Effect of a novel Omegacoeur®/Doluperine® nutritional combination on human embryonic kidney cell viability - Sottejeau, Y.; Patel, A. M.; Gerber, G.; Pierre, S. V.; Maixent, J. M. (Cellular and Molecular Biology, 2010)
Holistica Laboratories (Eguilles, France) developed the nutritional supplements Omegacoeur® and Doluperine® based on two of the most ancient and unique dietary health traditions. Omegacoeur® is formulated to supply key active components of Mediterranean diet (omega 3,6,9 fatty acids, garlic, and basil) and the formulation of Doluperine® was based on the Ayurvedic tradition (curcuma, pepper, ginger extracts). Interestingly, recent studies suggest that an combination of the ingredients supplied by these two supplements could provide additional and previously unanticipated benefit through synergistic actions of some of their key components. However, the effect of such combination on human cell viability has not been investigated. In this present article, a review of the various effects of the individual compounds of the new combination and the reported active doses, and the result of a study of an combination of Omegacoeur® / Dolupérine® on Human Embryonic Kidney (HEK 293) cells. Incremental doses of 4 Omegacoeur® / Dolupérine® combinations prepared so that the molar ratio DHA (Docosahexaenoic acid) in Omegacoeur® / curcumin in Dolupérine® was kept constant, at 2.5 DHA / 1 curcumin, were added to the culture media. After 24h of incubation, cell viability was assessed by the trypan blue exclusion method. The data suggest that the combination of Omegacoeur® with Dolupérine® does not affect HEK 293 cells viability in the range of doses that have demonstrated beneficial effects in earlier studies.